How do people in Ga-Rankuwa Township understand high blood pressure? - R.J. Henbest; N.H.B. Malete; E. McLeod; M. Tau (South African Family Practice)
Purpose: Hypertension is a common and important health problem. In spite of effective treatment being available, it is often poorly controlled. One reason for this is lack of compliance by patients with treatment because they do not feel ill. In recognition of the importance of the subjective aspects of patient care, this study sought to determine how people in Ga-Rankuwa Township understand high blood pressure. Method: The study was conducted in Ga-Rankuwa, South Africa, a large black township, Northwest of Pretoria. Two main samples participated: people attending the major shopping complex known as Ga-Rankuwa City, and patients attending the local government health care facilities; namely: Ga-Rankuwa Hospital and 3 community-based clinics. This study was part of a larger study done to determine whether patients could tell if their blood pressure was up. This part of the study consisted of an open-ended interview, using free attitude techniques that began by asking the participants in their language of choice "What is your understanding of high blood pressure?" Results: A total of 1004 people participated (a response rate of 97%) ranging from 16 to 88 years in age. Eleven interrelated themes were identified: lifestyle, symptoms, don't know, problems/stress/emotions, too much blood, people at risk, danger, physiology, chronic, environment and body heat. A model, integrating these themes is presented. Conclusion: It would seem that the themes identify thoughts that come from two main sources: one being the participants' own understanding of high blood pressure based on personal beliefs and experiences, the other being patient education. The personal understanding can be expressed as body heat. Perhaps one practical message from this study is that when you next see a patient with elevated blood pressure, you should find out what is generating his or her heat!